FISCAL-MONETARY POLICY INTERACTION. SVAR EVIDENCE FROM A CEE COUNTRY - Ana-Maria Cazacu (Bancu) (European Scientific Journal, ESJ, 2015)
The mix between monetary and fiscal policy actions are of vital importance on economic outcomes. The present paper integrates monetary and budgetary shock into a Structural Vector Autoregression (SVAR) model of Romanian economy. The policy mix, as well as the impact of the two policies on output gap and inflation is analyzed by means of both contemporaneous and long term identification schemes. The results over the 2000-2014 period, although generally in line with economic theory, provide no clear evidence on the strategic interaction (substituent or complementary instruments) between the monetary and public authorities. However, Granger causality and variance decomposition point to a relatively higher importance of monetary shocks in the economy.